(untitled) (Innovation & Development in Engineering and Applied Science, 2023)
This documentary-descriptive research aims to explore the advancement of artificial intelligence (AI) in selfdriving vehicles and its impact on the benefit of society. While it is undeniable that self-driving vehicles have practically become a technological reality in the field of computing, both at present and in the foreseeable future. However, several apparent problematic aspects need to be addressed in terms of legislation, as autonomous cars are set to become an integral part of everyday life. Therefore, this research examines through a literature review the significant advances and efforts devoted to software design in this area of study focused on the operation of autonomous vehicles in urban environments and their ability to circumvent city obstacles as well as challenges to unforeseen eventualities.